The Effect of Using the Teams Games Tournament (TGT) Model Assisted by TTS on the Students Interests and Learning Outcomes in Colloid Material - Christianto, Heru; Parera, Lolita A.M; Alunat, Duarancy (Jurnal Inovasi Pembelajaran Kimia (Journal of Innovation in Chemistry Education), 2023)
The purpose of this study was to determine the effect of learning the Teams Games Tournament type assisted by crossword puzzles (TTS) media on the interests and learning outcomes of Class XI MIA SMA Terpadu Hati Tersuci Maria Halilulik Academic Year 2021/2022. This research was conducted in a control class, colloidal system material was taught using a conventional model, while in the experimental class using the Teams Games Tournament type learning model assisted by crossword puzzles (TTS) for 4 meetings. For students' interest in learning, both classes were given questionnaires before and after learning activities. The results of the research hypothesis test showed that there were significant differences in interest and learning outcomes between students who were taught using the Teams Games Tournament type learning model in the form of crossword puzzles (TTS) and students who were taught using conventional learning models. The t-test results obtained sig.2-tailed value <5% significant level, namely 0.02<0.05 so that H0 was rejected and H1 was accepted.Keywords: Teams Games Tournament, Crossword Puzzles, Interest in Learning, Learning Outcomes